Book reviews - Steensgaard, Peter; Martola, Nils (Nordisk judaistik/Scandinavian Jewish Studies, 1988)
Kabbalah. En rejse i jødisk mystik (Judith Winther, 1986) is reviewed by Peter Steensgaard.Religion och samhälle i Mellanöstern (eds. J-O Blichfeldt & J. Hjärpe, 1985) is reviewed by Nils Martola.